2018
DOI: 10.1016/j.scitotenv.2017.10.323
|View full text |Cite
|
Sign up to set email alerts
|

Rapid prediction of total petroleum hydrocarbons concentration in contaminated soil using vis-NIR spectroscopy and regression techniques

Abstract: Visible and near infrared spectrometry (vis-NIRS) coupled with data mining techniques can offer fast and cost-effective quantitative measurement of total petroleum hydrocarbons (TPH) in contaminated soils. Literature showed however significant differences in the performance on the vis-NIRS between linear and non-linear calibration methods. This study compared the performance of linear partial least squares regression (PLSR) with a nonlinear random forest (RF) regression for the calibration of vis-NIRS when ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 30 publications
6
67
1
1
Order By: Relevance
“…() (1712 and 1752 nm) and Douglas et al . () (1712 and 1758 nm) for hydrocarbon‐contaminated soils. The wavelength of 2207 nm is near to those reported by Chakraborty et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…() (1712 and 1752 nm) and Douglas et al . () (1712 and 1758 nm) for hydrocarbon‐contaminated soils. The wavelength of 2207 nm is near to those reported by Chakraborty et al .…”
Section: Resultsmentioning
confidence: 99%
“…Results also showed that the PLSR model performed better for PAHs than for alkanes, with good performance in cross‐validation ( R 2 = 0.76, RMSEP = 0.81 mg kg −1 and RPD = 2.07) and fair performance in prediction ( R 2 = 0.56, RMSEP =1.21 mg kg −1 and RPD = 1.55) (Table and Figure ). The better performance of RF compared with PLSR can be attributed to the fact that the RF modelling technique typically yields better results when the relation between reflectance and concentration is nonlinear (typical in soils) (Nawar et al ., ; Douglas et al ., ), whereas the PLSR model fits only linear relations (Nawar et al ., ). Results obtained with PLSR are not as good as those already reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil samples were collected from three oil spill sites (Site 1:6.4527 o E, 5.1542 o N; Site 2: 6.4511 o E, 5.1357 o N; Site 3: 6.1224 o E, 4.9314 o N) in the Niger Delta region of Nigeria (Figure 1). For more details on the studied area and samples used (e.g., sampling location, method for sample collection, sampling depth, mass of samples, and sample preservation) readers are kindly referred to the study [22].…”
Section: Study Area and Soil Samplingmentioning
confidence: 99%
“…Reflectance spectroscopy has been successfully used to quantitatively measure petroleum hydrocarbons in a range of soil types (Forrester et al 2013;Okparanma and Mouazen 2013;Okparanma et al 2014;Douglas et al 2018). In addition, XRF has been used to successfully measure heavy metal concentrations in soils affected by human activities (Carr et al 2008;Radu et al 2013).…”
Section: Introductionmentioning
confidence: 99%